Pengetahuan dan Sikap Residen Obstetri dan Ginekologi tentang Keselamatan Pasien di Kamar Bersalin RSUP Dr. Sardjito Yogyakarta - Armaijn, Fadhilah; Emilia, Ova; Rachman, Irwan Taufiqur (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2016)
Background: The traditional medical Oath of ‘first do no harm’ is something that is very rarely breached either intentionally by a doctor, nurse or other health practitioner. Resident is health workers who perform services directly to patients that’s why their knowledge and attitudes towards patient safety are very usefulObjective: To determine the relationship of the level of knowledge with the attitudes about patient safety in obstetrics and gynecology resident while services in delivery room at Dr DR Sardjito hospital.Method: Descriptive methods with cross sectional approach, accompanied by a qualitative research The study involved 90 residents of Obstetrics and Gynecology at Sardjito Hospital Yogyakarta , by filling out a questionnaire. Knowledge assessed based on the number of correct answers and categorized into good and bad. Attitudes toward patient safety was assessed using a Safety Attitude Questionnaire (SAQ) labor and delivery version. Reliability was measured using Cronbach’s alpha. The qualitative data collection (interviews) conducted to support the descriptive data.Result and Discussion: Cronbach’s Alpha value for SAQ= 0.862, and the question of knowledge = 0.702. Between 77 responden who had good level of knowlage, only 53,2% had a good level of attitudes, and between 13 who has bad level of knowlage, there were 10 responden with good level of attitudes (76,9%) (RP 0,69;95%CI 0,44-1,04; p= 0,11). Elements of stress recognition on the attitude were getting the lowest average value (3.50 ± 0.56). From the qualitative data were known that the resident had desire for a reduction in working hours as well as improved communication and collaboration between teams. Althogh most of resident had a good level of knowledge and attitudes about patient safety, there were no meaning because of p value was >0,05 (OR 2,69;95%CI 0,66-10,9; p= 0,17).Conclusion: Clinically, a good level of knowledge about patien safety improving a good level of attitude towards patient safety.Keywords: Knowledge- attitude- patient safety- resident obstetrics